2020
DOI: 10.26656/fr.2017.4(4).415
|View full text |Cite
|
Sign up to set email alerts
|

The effect of processed Tempeh Gembus to triglycerides levels and insulin resistance status in women with obesity

Abstract: Obesity is an increasing weight that exceeds the limits of physical and skeletal needs due to the excessive backfilling of body fat. Obesity is a predisposing factor for increasing triglyceride levels (TG) and insulin resistance status. Consumption of fiber, such as Tempeh Gembus can be an alternative treatment to lower TG levels and insulin resistance status. This research was aimed to prove the influence of processed Tempeh Gembus to TG levels and insulin resistance status. This research employed a pre-post … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 37 publications
(44 reference statements)
0
11
0
Order By: Relevance
“…Like vinegar, many BFFs contain acetic acid and short chain fatty acids. Out of 19 studies which measured glucose outcomes, our review found that only six studies [53,60,[64][65][66]73,75] of different BFFs had significant improvements in some aspect of glycaemic control (FBG, HbA1c, FBI, 2hPPG and 2hPPI). Importantly, BFF subgroups, such as fermented kimchi, did not have the same effects on glycaemic control across all studies, which may be due to differences in study length, dosage and study populations.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Like vinegar, many BFFs contain acetic acid and short chain fatty acids. Out of 19 studies which measured glucose outcomes, our review found that only six studies [53,60,[64][65][66]73,75] of different BFFs had significant improvements in some aspect of glycaemic control (FBG, HbA1c, FBI, 2hPPG and 2hPPI). Importantly, BFF subgroups, such as fermented kimchi, did not have the same effects on glycaemic control across all studies, which may be due to differences in study length, dosage and study populations.…”
Section: Discussionmentioning
confidence: 96%
“…Overall risk of bias was low in 54% of studies, of some concern in 38% and high in 8%. Risk of bias during the randomisation process was low in all but ten studies: eight were of some concern, [53][54][55][56][57][58][59][60] and two were at high risk. [61,62] These ten studies did not describe randomisation or allocation concealment methods in enough detail.…”
Section: Assessment Of Risk Of Biasmentioning
confidence: 99%
See 3 more Smart Citations